2018
DOI: 10.1021/acsami.8b04557
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Biodegradable Black Mesoporous Silicon Nanoparticles for Highly Efficient Photothermal Therapy

Abstract: Porous silicon (PSi) has attracted wide interest as a potential material for various fields of nanomedicine. However, until now, the application of PSi in photothermal therapy has not been successful due to its low photothermal conversion efficiency. In the present study, biodegradable black PSi (BPSi) nanoparticles were designed and prepared via a high-yield and simple reaction. The PSi nanoparticles possessed a low band gap of 1.34 eV, a high extinction coefficient of 13.2 L/g/cm at 808 nm, a high phototherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 43 publications
(73 reference statements)
1
45
0
Order By: Relevance
“…We firstly detected differential gene expression when cells fed with the dual PEG functional black porous silica nanoparticles (BPSi NPs) (offered by our collaborating lab [12]). The change of the zeta potential from − 18.5 to + 2.8 mV also indicated that the surface dual-PEGylation was successful (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We firstly detected differential gene expression when cells fed with the dual PEG functional black porous silica nanoparticles (BPSi NPs) (offered by our collaborating lab [12]). The change of the zeta potential from − 18.5 to + 2.8 mV also indicated that the surface dual-PEGylation was successful (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The BPSi nanoparticles were prepared by our previous method [12] and supplied by our collaborator (Wujun Xu, Department of Applied Physics, University of Eastern Finland). The preparation of BPSi, NaSi, ammonium salt, and NaBr (NaSi: NH 4 Br: NaBr of 1:4:4, w/w/w) was ground in a glove box with an Ar atmosphere.…”
Section: Bpsi Nanoparticle Synthesismentioning
confidence: 99%
“…We firstly detected differential gene expression when cells fed with the dual PEG functional black porous silica nanoparticles (BPSi NPs) (offered by our collaborating lab [11]). Based on the Cluster heat map of differential gene expression ( Figure S1), we selected more than 2 fold differential gene expressions for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The BPSi nanoparticls were prepared by our previous method [11], and supplied by our collaborator (Wujun Xu, Department of Applied Physics, University of Eastern Finland).…”
Section: Bpsi Nanoparticles Synthesismentioning
confidence: 99%
“…In our previous study, 22 a new type of black mesoporous silicon (BPSi) nanoparticles was developed via the chemical oxidation method. The BPSi nanoparticles possessed better photothermal performance than gold nanoparticles, carbon nanotubes, and Fe 3 O 4 , 22 which have widely been studied as contrast agents in photoacoustic imaging. 10 , 12 , 23 Therefore, due to their outstanding photothermal performance, we hypothesize that the BPSi nanoparticles can serve as novel contrast agents to enhance the imaging sensitivity of PAT.…”
Section: Introductionmentioning
confidence: 99%